Adherence to neonatal sepsis clinical practice guideline according to type of sepsis in a Maternal Perinatal Institute of Lima, Peru - Dávila Aliaga, Carmen Rosa (2023)
Objective: The objective of this research is to describe adherence to the neonatal sepsis clinical practice guideline according to the type of sepsis in a perinatal maternal institute in Lima, Peru. Method: A descriptive study was carried out between the months of June to December 2021 at the Instituto Nacional Maternal Perinatal (INMP). The adherence of care to the CPG for the prevention, diagnosis and treatment of neonatal sepsis based on the INMP evidence was evaluated. Medical care was evaluated by two physicians who reviewed compliance or not with the 16 CPG recommendations. Adequate adherence was considered to be compliance of 80% or more of the recommendations established by the guideline in one care. Global adherence was calculated in percentages, by dimensions, by item and according to maternal and perinatal characteristics of care. Results: A total of 968 medical attentions were evaluated, of which 553 were early neonatal sepsis cases and 435 late. For early sepsis, an adherence of 84.4% was found, while for late sepsis, 66.8% was found. The lowest percentage of adherence was found in recommendations 2.7 and 3.2 of late sepsis care. Conclusions: An adequate adherence was found in early neonatal sepsis care, while, in relation to late neonatal sepsis, an adequate level of adherence was not reached.